PENERAPAN MODEL REACT BERBANTUAN PhET SIMULATION UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MOMENTUM DAN IMPULS - Afifah, Nur; Silitonga, Haratua Tiur Maria; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to identify the effectiveness of the implementation ofREACT Learning models assisted by PhET Simulation to improving students problem solving abilities in momentum and impulses material in Senior High School 1 Sungai Ambawang. This research uses pre-experimental design with the design one group pretest-posttest. The samples were students of class X MIPA 1 with total of 30 students chosen by means of intact group.Â  The students' problem solving abilities were measured using 5 instrument test descriptions. Obtained data problem solving abilities of students before given treatment (pretest) with an average percentage of 13,216% categorized as very less and has increased to 49.25% categorized as sufficient. Wilcoxon statistical test results obtained Asym.sig 2-Tailed of 0,000 (<0.05) which shows that there are significant differences in the students' pretest and posttest results. The effectiveness of the application of the REACT learning model assisted by PhET simulation was calculated by using the Cohen effect size formula and the results obtained were 3.05 and classified as high. The implementation of the REACT learning model assisted by PhET simulation can be used as an alternative in improving students' problem solving abilities, especially about momentum and impulses.Keywords:Momentum and impulses, PhET Simuation, Problem solving abilities,REACT learning models